Properties of chars from the gasification and pyrolysis of rice waste streams towards their valorisation as adsorbent materials. (July 2017) - Dias, D.; Lapa, N.; Bernardo, M.; Godinho, D.; Fonseca, I.; Miranda, M.; Pinto, F.; Lemos, F.
Graphical abstract: Highlights: Three major rice wastes are valorised through gasification and pyrolysis. Chars are characterised for chemical, textural and ecotoxic properties. Pyrolysis chars need to be further activated to be used as adsorbents. Gasification chars have the best properties to be valorised as adsorbents. Gasification chars can be valorised with no previous activation process. Abstract: Rice straw (RS), rice husk (RH) and polyethylene (PE) were blended and submitted to gasification and pyrolysis processes. The chars obtained were submitted to textural, chemical, and ecotoxic characterisations, towards their possible valorisation. Gasification chars were mainly composed of ashes (73.4–89.8 wt%), while pyrolysis chars were mainly composed of carbon (53.0–57.6 wt%). Silicon (Si) was the major mineral element in all chars followed by alkaline and alkaline-earth metal species (AAEMs). In the pyrolysis chars, titanium (Ti) was also a major element, as the feedstock blends contained high fractions of PE which was the main source of Ti. Gasification chars showed higher surface areas (26.9–62.9 m 2 g −1 ) and some microporosity, attributed to porous silica. On the contrary, pyrolysis chars did not present a porous matrix, mainly due to their high volatile matter content. The gasification bed char produced with 100% RH, at 850 °C, with O2 as gasification agent, was selected for further characterization. This char presented the higher potential to be valorised as adsorbent material (higher surface area, higher content of metal cations with exchangeable capacity, and lowest concentrations of toxic heavy metals). The char was submitted to an aqueous leaching test to assess the mobility of chemical species and the ecotoxic level for V. fischeri . It was observed that metallic elements were significantly retained in the char, which was attributed mainly to its alkaline character. This alkaline condition promoted some ecotoxicity level on the char eluate that was eliminated after the pH correction.